Predisposing factors of sugarcane abandonment in Rio de Janeiro: exploring policy implications - Castro, Pedro; Lautenbach, Sven; Vicens, Raúl (Land use policy, 2026)
Cropland abandonment is an agricultural land use change with notable socioeconomic and environmental implications. Previously managed fields are no longer cultivated and undergo natural succession. Biophysical, socioeconomic, and institutional factors that drive cropland abandonment differ between regions across the globe. In Brazil, Rio de Janeiro State has been showing a strong loss of cropland areas since the end of the 1980s. Especially sugarcane fields have become abandoned. This study used a spatial regression approach (spatial eigenvector mapping) to unveil the influence of biophysical and distance/cost-related factors on sugarcane abandonment in Rio de Janeiro. The results showed that both average precipitation and precipitation variability strongly influenced the amount of sugarcane abandonment: areas with higher precipitation variability and lower average precipitations in wet and dry seasons were more susceptible to abandonment. Sugarcane abandonment occurred mainly in steep areas outside the coastal tablelands. Access to markets, such as the road network distance to active sugar mills, also showed a significant positive relationship with sugarcane abandonment. Interestingly, the presence of protected areas - as a legal constraint - and Euclidean distance to roads and river channels were not significantly associated with sugarcane abandonment in our study region. The study sheds light on the impact of water scarcity on the sugarcane farming development in the Norte Fluminense region.